Dialogul teologic actual între Biserica Ortodoxă și Bisericile Ortodoxe orientale - Cojocaru, Sorin (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
In this study we first set out to clarify the causes and current consequences of Chalcedon Christology. On the other hand, we focused on the most significant documents of the current theological dialogue of the second half of the twentieth century, which resulted from unofficial and later official meetings between the two branches of Orthodoxy, the Orthodox Church as a whole, and the Old Eastern or non-Chalcedonian Churches, which rightly deserve the title of Eastern Orthodox Churches they received in 1985, at the beginning of the official dialogue between them. A special attention was paid to the different styles of dialogue and theological consensus in order to highlight the specific features of the orthodox style of ecclesiological consensual dialogue.